Peran Guru Kristen sebagai Pemegang Otoritas untuk Meningkatkan Disiplin Siswa dalam Pembelajaran [The Role of Christian Teachers in Exercising Authority to Improve Discipline in Learning] - Gabriela Adhielvra; Asih Enggar Susanti (Universitas Pelita Harapan, 2020)
Disipline can produce effective condition for learning. But the observation result in one of the schools in Tangerang showed that students lack discipline as they participate in learning. They were impolite, showing lack of respect for teachers, lazy, and refused to comply to agreed rules and procedures in class. Therefore, it was necessary for the teacher as one with authority to be firm so that the learning process could be conducive. This paper aims to examine the important role of teachers in exercising authority in learning. It is necessary for Christian teachers to exercise the God-given authority to discipline students to ensure effective learning. The result of the study shows that Christian teachers can exercise authority to improve discipline in students It can be concluded that the authority of Christian teachers has an important role to improve discipline in students. The suggestion is for teachers to be firm ant to exercise their authority wisely in accordance with God’s word. For further research, it is suggested that the next researcher uses the required support instrument and add the indicator of the teacher’s firmness to measure the influence of the teacher’s authority on the students’ discipline in learning. Hence, a more comprehensive data can be obtained and a deeper research can be conducted.